STRATEGI MENINGKATKAN KINERJA PEGAWAI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI KANTOR KEMENTERIAN AGAMA KOTA SERANG - Sobariah, Iis; Sanusi, Fauji; Yazid, Helmi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
The purpose of this research to know influence intrinsic motivation, transformational leadership on discipline to improve employee performance. Independent variable in this research is intrinsic motivation and transformational leadership, the dependent variable is employee performance, and the intervening variable is discipline. This research is held in Kantor Kementerian Agama Kota Serang. The sample is 75 (seventy-five) respondents. The primary data were collected using a questioner that consist of a statement list and analyzed by SEM (Structural Equation Modelling) using SmartPLS statistic software. Five hypotheses constructed in this research there were forth hypotheses are accepted, intrinsic motivation is influential positive and significant on discipline, transformational leadership is influential positive and significant on discipline, transformational leadership is influential positive and significant on employee performance, and discipline is influential positive and significant one employee performance. While one other hypothesis is rejected, intrinsic motivation is influential positive but not significant on employee performance.